2019
DOI: 10.1091/mbc.e19-02-0076
|View full text |Cite
|
Sign up to set email alerts
|

Myosin IIA–mediated forces regulate multicellular integrity during vascular sprouting

Abstract: Angiogenic sprouting is a critical process involved in vascular network formation within tissues. During sprouting, tip cells and ensuing stalk cells migrate collectively into the extracellular matrix while preserving cell–cell junctions, forming patent structures that support blood flow. Although several signaling pathways have been identified as controlling sprouting, it remains unclear to what extent this process is mechanoregulated. To address this question, we investigated the role of cellular contractili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 70 publications
3
30
0
Order By: Relevance
“…Our results from singly NM2A or NM2B endothelial cell-ablated mice and 3D EB angiogenic sprouting show that NM2A, but not NM2B, is required for sprouting angiogenesis. Similar findings are reported for a 3D biomimetic model of angiogenesis using HUVECs by CRISPR ablation of NM2A and 2B individually ( Yoon et al. , 2019 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results from singly NM2A or NM2B endothelial cell-ablated mice and 3D EB angiogenic sprouting show that NM2A, but not NM2B, is required for sprouting angiogenesis. Similar findings are reported for a 3D biomimetic model of angiogenesis using HUVECs by CRISPR ablation of NM2A and 2B individually ( Yoon et al. , 2019 ).…”
Section: Discussionsupporting
confidence: 85%
“…, 2018 ). Recently, it was shown that application of blebbistatin or Y27632 and deletion of the NM2A paralog in endothelial cells disrupts cell–cell adhesion and results in endothelial cell scattering in a 3D angiogenic sprouting culture of human umbilical vein endothelial cells ( Yoon et al. , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11–14 ] Researchers have therefore begun to engineer dynamic interactions between cells and ECM in order to guide multi‐cellular structure formation. [ 15–24 ] For example, Davidson et al found that networks of contractile endothelial cells with different morphologies could be generated by varying the extent to which cells were able to physically reorganize surrounding ECM fibers. [ 25 ] Brownfield et al also found that mammary epithelial organoids reorganize and align collagen I fibers through cell contractility, and form multi‐cellular protrusions that follow preferentially along the axis of ECM alignment.…”
Section: Figurementioning
confidence: 99%
“…Blebbistatin is a myosin II inhibitor, and it regulates microtubule assembly and myosin-actin interactions. The activity of blebbistatin on the cytoskeleton has been shown to be involved in the regulation of cell structure, morphology (Yoon et al, 2019), and migration (Hu et al, 2019;Wang et al, 2019) and to maintain the survival and growth of stem cells (Zhao et al, 2015) and to reduce oxidative stressinduced apoptosis. Blebbistatin protects Lgr5+ stem cells against colitis-induced epithelium injury in gastrointestinal tissues through the Myh9-Rac1-PAK1-Akt pathway (Zhao et al, 2015) and induces cell migration through myosin-II-related matrix stretch and recoil (Vicente-Manzanares et al, 2009).…”
Section: Discussionmentioning
confidence: 99%